<em>1) 5 c + 4 = - 26
5 c = -26 -4
5 c = -30
c = -30 / 5
c = -6 so correct option is B..
2) 3 x - x +2 = 12
2 x +2 = 12
2x = 12-2
2x = 10
x = 10/2
x= 5 so correct option is D
3 ) 3 ( x + 1 )+ 6 = 33
3x + 3 + 6 = 33
3x + 9 = 33
3x = 33-9
3x = 24
x = 24/3
x = 8 so correct option is B
4) y/-6=9
y=9 x -6
y= - 54 there is no such option i guess question is missing
5)(x + 4) /2 = 7
x +4 = 7 x 2
x + 4 = 14
x = 14-4
x = 10 so correct option is D
6)1/3 ( 2x - 8) = 4
2x/ 3 - 8 /3 = 4
2x - 8 / 3 = 4
2x - 8 = 4 x 3
2x - 8 = 12
2x = 12 + 8
2x = 20
x = 20/2
x = 10 so correct option is C
</em>
Answer:
what
Step-by-step explanation:
sure?
First you should combine n/6-5n/12
that goes to 2n/12-5n/12 which equals -3n/12
then you should cross multiply -3n/12 by 1/16
12(1)=-3n(16)
12=-48n then solve for n by dividing by -48
-12/48=n simplify -1/4=n or -.25=n
Answer:
x=1
Step-by-step explanation:
slope AB = (7-5) / (3 - -1) = 2 / 4 = 1/2
slope CD = (23-11) / (x-7) = 12 / (x-7)
12 / (x-7) = - 2 ... perpendicular to AB slope 1 = - 1/slope 2
-2 (x-7) = 12
-2x + 14 = 12
-2x = -2
x = 1
Answer:
84mm^3
Step-by-step explanation:
multiply 12 by 7